Transformational Leadership on Performance: Mediating Role of Flexible Work Arrangements and Work Engagements (Study on the Coffee Shop Industry in Yogyakarta) - Jauhar, Muhammad Faiq; Suratman, Andriyastuti (International Business Management - Universitas Ciputra, 2022)
This study deals with the effect of transformational leadership and flexible work arrangement on performance through work engagement as an intervening variable in the cafe industry in Yogyakarta. The purpose of this study was to determine the effect of the variables to be studied, namely transformational leadership, flexible work arrangement, work en- gagement, and performance. Respondents in this study were 106 workers from 34 cafes in Yogyakarta. The data collection method in this study used a questionnaire with 5 Likert scales. The results of this study indicate that there is a positive effect of the variables tested for both direct and indirect impact. However, the value is not greater than the immediate effect. This research aims to increase the opportunities for determining flexible work arrangements, strengthening transformational leadership, especially em- ployee motivation and involvement, and maintaining performance through a suitable communication process.